Pengaruh Marketing Mix 4C Dan Brand Image Terhadap Purchase Decision Pada Produk Bir Bintang Di Bali - Luh Komang Candra Dewi; Sili Antari; Denny Trisna Ardana (RELASI : JURNAL EKONOMI, 2022)
This research aims to analyze the the effect of marketing mix 4c (customer value, cost, convenience and communication) and brand image on purchase decision by Bir Bintang’s consumers. Respondents in this research were Bir Bintang’s consumers who lived in Bali with 150 respondents in total. The sampling technique that used in this research is purposive sampling by consider the age criteria of Bir Bintang’s consumers above 21 years up to 50 years, as well as quota sampling technique which proportionally divides the entire sample per each of district and city in Bali Province. Methods of data collection using a questionnaire through the media google form.The analysis technique used in this research is multiple linear regression with software SPSS 24.0 for Windows. The results showed that the variable of customer value and cost are partially has no significant effect on the Bir Bintang purchase decision. Meanwhile the variable of convenience, communication and brand image are partially has significant effect on the purchase decision of Bir Bintang.The results of this research are expected to be used as a reference in the next further research, as well as a consideration for the company's management in developing future strategies. Keywords: marketing mix 4c, brand image and purchase decision.